Dispensing of antibiotics for tuberculosis patients using standardized patient approach at community pharmacies: results from a cross-sectional study in Pakistan - Gillani, Ali Hassan; Arshad, Hafsa; Mujtaba, Hasan; Umer, Muhammad Farooq; Xu, Sen; Ji, Wenjing; Bashir, Kamran; Chang, Jie; Yang, Caijun; Fang, Yu (Frontiers in Public Health, 2024)
Background Pakistan is among top countries for antibiotic consumption around the globe and patients often receive antibiotics directly from community pharmacies. Thus, our aim was to assess the drug dispensing practices of pharmacies for presumed and confirmed tuberculosis by using standardized patients’ method in Pakistan. Methods In this cross-sectional study, we adopted two standardized patient cases in pharmacies of three cities of Punjab. The first case involved a presumed tuberculosis patient presenting with 2–3 weeks of cough and fever (Case-1), and the second case involved a confirmed tuberculosis patient carrying microbiologically confirmed tuberculosis results (Case-2). The ideal management for Cases-1 and Case-2 is referral of standardized patients to a healthcare provider without dispensing antibiotics or steroids, or both. The differences in antibiotic use, steroid use, and the number of medicines dispensed in referred and non-referred patients between Case-1 and Case-2 were analyzed using descriptive statistics. Results Between April 1, 2020, and July 31, 2020, standardized patients completed 575 out of 598 interactions among community pharmacies in Lahore, Rawalpindi, and Sialkot. We recorded ideal management in 115 (37.7%) of the 305 Case-1 interactions and 130 (48.1%) of the 270 Case-2 interactions. Antibiotic dispensing was higher in Case-1, with 71 out of 305 instances (23.3%), than in Case-2 interactions, with 27 out of 270 instances (10.0%). Anti-tuberculosis drugs were dispensed to 1 patient in Case-1 (0.3%) and to 19 patients (7.0%) in Case-2. Conclusion Slightly more than one-third of pharmacies in Punjab, Pakistan, ideally managed patients with presumed tuberculosis, but almost half of them ideally managed cases of confirmed tuberculosis. The presence of confirmed diagnosis slightly changes the behavior in the correct management of patients.